Tindak Tutur Representatif Perkembangan Penyebaran Covid-19 dalam Berita di CNN Indonesia - Mahmudah Mahmudah; Endang Sumarti; Susandi Susandi (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
he focus of this research is (1) the formof representative speech acts on the development of the spread of covid -19 in news on CNN Indonesia and (2) the function of representative speechacts on the development of the spread of covid -19 in the news on CNN Indonesia. The approach used in this study is a qualitative approach. The data source of this research is news on the development of the spread of covid-19 on CNN Indonesia. The research instrument is the researcher himself as a key instrument. The data analysis technique in this study is an interactive model analysis technique. Based on the results of the data analysis of this study, the following findings were obtained. First, the form of representative speech acts developments Covid -19 Spreading the news on CNN Indonesia were found in this study include: speech acts statement, the speech act of demanding, speech act of acknowleding, speech acts of reporting, speech acts of showing, speech acts of saying, speech acts of provide testimony, and speech acts are speculative. Second, the function of representative speech acts on the Development of the Spread of Covid -19 in the News in Cnn Indonesia found in this study includes: the function of stating, the function of demanding, the function of acknowledging, the function of reporting, the function of showing, the function of saying, the function of giving testimony, and the function of speculating.